Hypoxia inducible factor 1alpha and 2alpha overexpression in inflammatory bowel disease. - Giatromanolaki, A; Sivridis, E; Maltezos, E; Papazoglou, D; Simopoulos, C; Gatter, K; Harris, A; Koukourakis, M (2003)
AIMS: Hypoxia inducible factors 1alpha and 2alpha (HIF1alpha and HIF2alpha) are hypoxia regulated transcriptional factors, which control the expression of a variety of genes responsible for angiogenesis, glycolysis, and the inhibition of apoptosis. Because angiogenesis and tissue regeneration are integral components of the inflammatory process, this study was designed to investigate the role of HIFalpha molecules in inflammatory bowel disease. METHODS: Surgical specimens from patients with active ulcerative colitis (UC) and Crohn's disease (CD) were assessed immunohistochemically for HIF1alpha and HIF2alpha reactivity, and the expression of these molecules was compared with the expression of the angiogenic factors thymidine phosphorylase (TP), vascular endothelial growth factor (VEGF), and VEGF-KDR activated vasculature. The vascular density of the lesions was also assessed using anti-CD31 immunostaining. RESULTS: HIF1alpha was expressed focally (epithelial cells, stromal fibroblasts, and myocytes) in both UC and CD, whereas HIF2alpha was expressed focally in UC and diffusely in CD. TP expression was uniformly positive in both diseases. VEGF expression was absent in CD, and weakly positive in UC. The VEGF-KDR reactivity of the submucosal vasculature was only slightly increased in UC and CD compared with normal tissue. The inflammatory cells stained with HIF2alpha and TP in all cases, but the reactivity was generalised in CD and focal in UC. In both diseases, vascular density was significantly higher than that seen in normal tissue. CONCLUSIONS: The discordant expression of HIF2alpha and VEGF in CD suggests an inherent deficiency of the intestine to respond to various stresses by the induction of VEGF. This finding should be investigated further.